Workshop Internet dan Digital Marketing untuk Meningkatkan Daya Saing Pada Kelompok Pengusaha Muda Ponorogo - Premi Wahyu Widyaningrum; Wira Bharata (Universitas Muhammadiyah Ponorogo, 2017)
The amount of convenience and functionality of the use of digital media encourages people or businessmen in the world to use digital media in all of activities. Another function of the use of digital media is branding, sharing, promoting, and marketing. The development of internet and information technology is also a great influence on the development in promoting the products. To achieve those objectives, the activity is carried out by workshop method in the form such as delivery of material, discussion, and simulation and practice the use of digital marketing. This activity is concerned for young entrepreneurs in Ponorogo. There are several criteria classified by author intended to young entrepreneurs. First, young entrepreneurs being objectives are those aged between 15-35 years. Second, they are neither a member of community nor incorporated with associations of entrepreneur in Ponorogo. Furthermore, they were still running the business, particularly in marketing the products by using conventional or traditional way. Through this activity, those young entrepreneur groups will have better understanding about the importance of using internet media in enhancing business competitiveness. The majority participants gave positive feedback on the implementation of this public service activity.